Population impacts in white sucker (Catostomus commersonii) exposed to oil sands–derived contaminants in the Athabasca River. (13th February 2017) - Arens, Collin J.; Arens, Jennifer C.; Hogan, Natacha S.; Kavanagh, Richard J.; Berrue, Fabrice; Van Der Kraak, Glen J.; van den Heuvel, Michael R.
Abstract: Biological and chemical endpoints were measured in white sucker collected downstream of Athabasca oil sands developments (AB, Canada) and compared with those at Calling Lake (AB, Canada), a reference location upstream of the Athabasca oil sands deposit. Naphthenic acid concentrations were also measured at 14 sites in the Athabasca River watershed. Concentrations of naphthenic acids were elevated in tributaries adjacent to oil sands mining developments. Tributary naphthenic acid profiles were more similar to aged oil sands process water than samples from the Athabasca River, suggesting an influence of tailings in the tributaries. White sucker showed higher energy storage in the Athabasca River as indicated by significantly higher condition and liver size. White sucker were not investing that energy into reproductive effort as measured by gonad size and fecundity, which were significantly reduced relative to the reference location. White sucker showed increased exposure to polycyclic aromatic hydrocarbons as indicated by hepatic cytochrome P4501A (CYP1A) activity and fluorescent bile metabolites, as well as higher concentrations of naphthenic acids in bile. Cadmium, copper, nickel, and selenium were also elevated in white sucker liver tissue compared with the reference location. Based on the exposure profile and response pattern observed, effects on energy storage and utilization in white sucker from the Athabasca River most likely resulted from exposure to polycyclic aromatic hydrocarbons derived from petrogenic and pyrolytic sources. Environ Toxicol Chem 2017;36:2058–2067. © 2017 SETAC